2001
DOI: 10.1002/mrd.1006
|View full text |Cite
|
Sign up to set email alerts
|

Protection against reactive oxygen species during mouse preimplantation embryo development: Role of EDTA, oxygen tension, catalase, superoxide dismutase and pyruvate

Abstract: Oxidative damage due to the production of reactive oxygen species (ROS) is one of a number of culture-induced stresses which may compromise preimplantation embryo development in vitro. Ethylenediaminetetraacetic acid (EDTA), reduced oxygen tension, superoxide dismutase (SOD) and catalase (CAT) offer protection against oxidative stress, but few attempts have been made to determine which of these agents, or which combination, is the most effective. In particular, no systematic investigation of their actions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
90
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(94 citation statements)
references
References 42 publications
4
90
0
Order By: Relevance
“…A very straightforward hypothesis is that incubation with H 2 O 2 might increase the level of antioxidants in the oocyte and/or cumulus cells with a positive effect on their future development. Increased levels of antioxidants may improve embryo development to the blastocyst stage as demonstrated for catalase (Li et al 1993, Orsi & Leese 2001, GSH (Luvoni et al 1996, Abeydeera et al 1999, de Matos & Furnus 2000, de Matos et al 2002, Ozawa et al 2006, and superoxide dismutase (Li et al 1993, Chun et al 1994 in different species. GSH content at the end of maturation has been identified as a reliable indicator of oocyte viability (Abeydeera et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A very straightforward hypothesis is that incubation with H 2 O 2 might increase the level of antioxidants in the oocyte and/or cumulus cells with a positive effect on their future development. Increased levels of antioxidants may improve embryo development to the blastocyst stage as demonstrated for catalase (Li et al 1993, Orsi & Leese 2001, GSH (Luvoni et al 1996, Abeydeera et al 1999, de Matos & Furnus 2000, de Matos et al 2002, Ozawa et al 2006, and superoxide dismutase (Li et al 1993, Chun et al 1994 in different species. GSH content at the end of maturation has been identified as a reliable indicator of oocyte viability (Abeydeera et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In a mice model, Orsi and Leese [21] showed that a 5 % O 2 concentration significantly contributed to enhancing embryo development and also increased cell numbers.…”
Section: Discussionmentioning
confidence: 99%
“…AKR1B1, with superoxide dismutase-2 and metallothioneins, may act to protect cells from unstable reactive radicals and heavy metals implicated in the pathology of a number of organs including endometrium (Kagi 1991, Ishikawa et al 1993, Sies 1993. These toxic compounds and oxygen free radicals may be detrimental to the attachment, implantation and development of the embryo (Orsi & Leese 2001) and AKR1B1 may play a role around the time of implantation to protect the embryo and to create a safe environment for reception of a fertilised ovum. Similarly at menstruation, these proteins may serve to mop up free radicals generated by highly activated leukocytes during tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%